If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -9p(-6p + 2) = -2p + -9 Reorder the terms: -9p(2 + -6p) = -2p + -9 (2 * -9p + -6p * -9p) = -2p + -9 (-18p + 54p2) = -2p + -9 Reorder the terms: -18p + 54p2 = -9 + -2p Solving -18p + 54p2 = -9 + -2p Solving for variable 'p'. Reorder the terms: 9 + -18p + 2p + 54p2 = -9 + -2p + 9 + 2p Combine like terms: -18p + 2p = -16p 9 + -16p + 54p2 = -9 + -2p + 9 + 2p Reorder the terms: 9 + -16p + 54p2 = -9 + 9 + -2p + 2p Combine like terms: -9 + 9 = 0 9 + -16p + 54p2 = 0 + -2p + 2p 9 + -16p + 54p2 = -2p + 2p Combine like terms: -2p + 2p = 0 9 + -16p + 54p2 = 0 Begin completing the square. Divide all terms by 54 the coefficient of the squared term: Divide each side by '54'. 0.1666666667 + -0.2962962963p + p2 = 0 Move the constant term to the right: Add '-0.1666666667' to each side of the equation. 0.1666666667 + -0.2962962963p + -0.1666666667 + p2 = 0 + -0.1666666667 Reorder the terms: 0.1666666667 + -0.1666666667 + -0.2962962963p + p2 = 0 + -0.1666666667 Combine like terms: 0.1666666667 + -0.1666666667 = 0.0000000000 0.0000000000 + -0.2962962963p + p2 = 0 + -0.1666666667 -0.2962962963p + p2 = 0 + -0.1666666667 Combine like terms: 0 + -0.1666666667 = -0.1666666667 -0.2962962963p + p2 = -0.1666666667 The p term is -0.2962962963p. Take half its coefficient (-0.1481481482). Square it (0.02194787382) and add it to both sides. Add '0.02194787382' to each side of the equation. -0.2962962963p + 0.02194787382 + p2 = -0.1666666667 + 0.02194787382 Reorder the terms: 0.02194787382 + -0.2962962963p + p2 = -0.1666666667 + 0.02194787382 Combine like terms: -0.1666666667 + 0.02194787382 = -0.14471879288 0.02194787382 + -0.2962962963p + p2 = -0.14471879288 Factor a perfect square on the left side: (p + -0.1481481482)(p + -0.1481481482) = -0.14471879288 Can't calculate square root of the right side. The solution to this equation could not be determined.
| 5(3z+7)=125 | | 1=12x^2+11x | | 15x^2-13x=0 | | 7x-6x=13+3x | | 5x^2-3x=8 | | 6x+8-2x(7-2)=2(6x+1) | | 4x^3-2x^2+12x=0 | | 2x^2=16x | | 36-6x=28 | | (x-9)(3x+1)=0 | | 3(4y+5)=51 | | 6(2g-5)=-6 | | x^2+9=6x | | 8x+16=2x+106 | | 2y+10=5y-4 | | 14x^2=0 | | 110-5x=22x+20 | | x(x+7)=15x-21 | | 21=1-5p | | 5=3+8b | | 11-10x=85-24x | | 10-2y=y+8 | | 6x*x+35x+48=x | | 12x-x^2=0 | | 4(x-2)-8x=3(1-x)-9 | | 6x+35x+48=8 | | -108-8x=10x+18 | | 47-6x=12x+19 | | 7-2m=12 | | 13x-x^2=0 | | x^3+3x^2-13x-15=0 | | 4-10r=34 |